Leveraging social networking sites for knowledge co-construction: Positive effects of argumentation structure, but premature knowledge consolidation after individual preparation. (December 2017) - Tsovaltzi, Dimitra; Judele, Raluca; Puhl, Thomas; Weinberger, Armin
Abstract: Social Network Sites (SNS) like Facebook bear potential for collaboration through rich social interactions, but the shared arguments are often poorly elaborated, and lack epistemic quality. In a controlled 2 × 2 study ( N  = 128), we investigated how individual preparation and argumentation scripts can support argumentative knowledge co-construction in Facebook. Individual preparation has been shown to motivate participants, activate prior knowledge, reduce process losses and promote unbiased arguments. Argumentation scripts can support quality of argumentative discussions and evidence-based argumentation. Their combination may, thus, enhance the argumentation quality in SNS interactions and facilitate domain knowledge acquisition. We found negative effects of individual preparation, ascribable to lack of knowledge co-construction and knowledge convergence, that point to knowledge consolidation. Scripting argumentation has some positive effects, but not in combination with individual preparation. We identify possibilities and risks of applying standard collaborative learning instructions in the context of SNS, and discuss theoretical consequences. Highlights: Individual preparation can hinder collaborative learning affordances in social networking sites. Learners may consolidate knowledge and persist on initial arguments when preparing individually. Argumentation scripts can support quality argumentation in collaborative social networking site discussions. Argumentation scripts can promote argumentative knowledge co-construction. Argumentation scripts could not counteract negative effects of individual preparation.